Vegetation of a Polylepis incarum forest (Rosaceae) in Lampa district, Puno, Peru - Montesinos-Tubée, Daniel B. (2015)
The vegetation of the Polylepis incarum (Bitter) M. Kessler & Schmidt-LeBuhn forests was studied in the Lamparaquen annex in the province of Lampa, Puno department in 2009 and 2014. A total of 83 vascular species belonging to 35 families were determined. The lifeforms are represented by herbs, grasses, shrubs and trees, being mostly native and endemic species with some introduced. The queñoal ecosystem is represented by the new phytosociological unit Lupino chlorolepis-Polylepidetum incari with four subassociations identified. The floristic composition shows a moderate to high species richness, being the most representative families, Asteraceae, Poaceae, Caryophyllaceae, Fabaceae and Pteridaceae. The Braun-Blanquet phytosociological method was applied for the analysis of the vegetation units. The classification of communities was done by means of TWINSPAN software, DCA ordination analysis with CANOCO 4.5 software and a dendrogram based on the correlation of species for each quadrant which was performed with PC-ORD software. Further studies are still needed to have a broader view of the plant communities in other geographic areas, and evaluate how vegetation may be affected by climate change and human actions.